Prostacyclin (epoprostenol) and heart-lung transplantation as treatments for severe pulmonary hypertension. Issue 4 (October 1993) - Higenbottam, T W; Spiegelhalter, D; Scott, J P; Fuster, V; Dinh-Xuan, A T; Caine, N; Wallwork, J
Abstract : OBJECTIVE--To determine whether epoprostenol (prostacyclin, PGI2) or heart-lung transplantation (HLT), or both improves survival of patients with severe pulmonary hypertension. DESIGN--This was a prospective study where the effects of epoprostenol were compared with conventional treatment. Also, the benefits of epoprostenol and HLT were assessed by comparing survival in this group with that of 120 patients at the Mayo Clinic before HLT and epoprostenol treatment became available. PATIENTS AND INTERVENTIONS--Forty four patients were studied; 25 received continuous epoprostenol over a four year period (mean (SD) cardiac index 1.8 (0.4) 1 min-1 m-2 and mean (SD) pulmonary artery pressure (PAP) 70 (16) mm Hg) and 19 did not (cardiac index 2.1 (0.6) 1 min-1 m-2 and PAP 64 (13) mm Hg). Ten patients underwent HLT: seven had received epoprostenol, and three had not. RESULTS--The therapeutic intervention with epoprostenol, or HLT, or both improved survival compared with the Mayo clinic patients (p = 0.05). Most of the benefit was conferred by epoprostenol, which prolonged survival twofold from a median time of eight to 17 months and doubled the changes of successful HLT. The improved survival with epoprostenol was not related to its immediate capacity to cause pulmonary vasodilation. Those patients who had limited acute pulmonary vasodilation when treated with epoprostenol showed the greatest improvement in survival. CONCLUSIONS--These preliminary results indicate that those pulmonary hypertensive patients with the poorest chance of survival can be helped by epoprostenol and by HLT.